PENGARUH PENGGUNAAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR TINGKAT TINGGI - Fajri Arif Wibawa (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2019)
Based on observations of problems that occur at MA Tuma'ninah Yasin Metro Class X IPS it can be seen that there are still many students who are not good in their high-level thinking skills. The lack of high-level thinking ability is due to several factors including the learning model used by the teacher that is not appropriate, inadequate facilities and infrastructure and others. So that efforts can be made to improve students' high-level thinking skills is the need for change. The purpose of this study was to determine the effect of the use of problem-based learning models on higher-order thinking skills. This research was conducted in MA Tuma'ninah Yasin Metro with a population in class X IPS with a total of 35 students and a sampling technique with saturated sample technique that is all populations were sampled. The research method used is experiment. The instruments in this study used a high-level thinking ability test item. Data analysis using t-test. The results showed that there was an influence of the use of problem-based learning models on the ability to think at a higher level. Keyword: problem based learning model, high-order thinking